FORMULATION AND CHARACTERIZATION OF TOPICAL NANO EMULGEL OF TERBINAFINE - Paliwal, Sonia; Kaur, Gurleen; Arya, Rajeshwar KK (Universal Journal of Pharmaceutical Research, 2019)
Objective: Terbinafine is a broad spectrum antifungal drug. The aim of present study was to develop topical nano emulgel of terbinafine using carbopol 934 as a gelling agent. The objective behind the formulation was to avoid dosing frequency and to increase the stability and bioavailability by avoiding the first pass metabolism. Methods: The formulations were prepared by using oleic acid, carbopol 934, span 20, propylene glycol in different ratios and analyzed by pseudo tertiary phase diagram. All the five prepared nano emulgel formulations have shown satisfactory physiochemical properties. The stability and particle size is been determined by zeta potential. Results: The highest drug release 82.38 %was found in formulations of batch F4, which follows non-fickian mechanism. The studies showed that changing the concentration of oil, surfactant, co surfactant and double distilled water as aqueous phase has an impact on the behavior and thermodynamic stability of the nanoemulsion. Conclusion: Study concludes that of Terbinafine can be delivered effectively by nano emulgel formulations. Peer Review History: Received 3 October 2018; Revised 11 November; Accepted 27 December; Available online 15 January 2019 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewer(s) detail: Dr. Mohamed Salama , Modern University for Technology & Information, Egypt, salama47@yahoo.com Dr. Mahmoud S. Abdallah , University of Sadat city, Egypt, dr_samy777@yahoo.com